The Requirement for Hydrographic Surveys in Ports and Anchorages - Sathaye, N. N. (The International Hydrographic Review, 2015)
The advent of larger, special-purpose ships in the last two decades has made big demands on a number of ports in the world since such vessels require deeper and wider channels than heretofore, as well as modern facilities to ensure their quick turn-around. Port Authorities have therefore had to undertake major projects requiring heavy investment for fear that shipowners would “by-pass” their port. This paper points out that accurate and comprehensive hydrographic data is a pre-requisite for any marine development scheme in a port. It cautions those unaware of this need by providing examples of cases where industry has incurred heavy losses and where there have been delays in commissioning new facilities precisely on account of this lack, or this insufficiency, of reliable hydrographic data. To avoid such pitfalls the paper recommends that Port Authorities should create their own hydrographic services to meet their conservancy requirements and also to undertake improvement of their existing facilities. Two existing port hydrographic services are briefly described to provide an idea of the diversity of requirements, their resources and manpower, and also how these ports in widely differing environments have dealt with their problems. Finally a suggestion is made as to how a modest organization can be set up to meet a port’s hydrographic requirements, and the sources for obtaining expert advice in this sphere are indicated.